2014
DOI: 10.1186/1472-6920-14-220
|View full text |Cite
|
Sign up to set email alerts
|

Five teacher profiles in student-centred curricula based on their conceptions of learning and teaching

Abstract: BackgroundTeachers’ conceptions of learning and teaching are partly unconscious. However, they are critical for the delivery of education and affect students’ learning outcomes. Lasting changes in teaching behaviour can only be realized if conceptions of teachers have been changed accordingly. Previously we constructed a questionnaire named COLT to measure conceptions. In the present study, we investigated if different teacher profiles could be assessed which are based on the teachers’ conceptions. These teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 51 publications
1
25
0
6
Order By: Relevance
“…These achievements can be predicted based on the type of strategy they have previously designed [ 11 , 14 , 15 ]. Recently, several studies have demonstrated that teachers’ conceptions of learning also affect, although indirectly, students’ learning outcomes [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These achievements can be predicted based on the type of strategy they have previously designed [ 11 , 14 , 15 ]. Recently, several studies have demonstrated that teachers’ conceptions of learning also affect, although indirectly, students’ learning outcomes [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we used the COLT questionnaire to measure teachers’ conceptions of learning and teaching in two student-centered medical curricula [ 8 ]. A cluster analysis resulted in five teacher profiles, ranging from a traditional profile aiming to transmit knowledge to a more modern profile aligned with student-centered education [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It took even more time for faculty to adjust to the small group teaching concept. In our research, we found that the perception of teaching and learning of faculty was still more teacher-centered than student-centered, even after 10 years of curricular change to small group teaching (Jacobs et al 2014). The second important lesson we learned is that it is important for a medical school to refresh its vision from time to time and align to the changing societal context, e.g.…”
Section: The Lessons Learned In Relation To the Development Describedmentioning
confidence: 79%